Pengembangan media pembelajaran PPKn kelas XI menggunakan Articulate Storyline di Madrasah Aliyah Muhammadiyah Tanjuang Bonai - septianti, ira; Usmanto, Heri (Citizenship Education, Faculty of Education, Jambi University, 2024)
The purpose of this study was to produce an android-based PPKn learning media with the help of Articulate Storyline software which was tested on class X1 students of Madrasah Aliyah Muhammadiyah Tanjuang Bonai. This development research was conducted using the ADDIE development model which includes Analysis, Design, Development, Implementation, and Evaluation. Validation was carried out by media experts with a percentage of 85%